Body composition parameters, immunonutritional indexes, and surgical outcome of pancreatic cancer patients resected after neoadjuvant therapy: A retrospective, multicenter analysis - Paiella, Salvatore; Azzolina, Danila; Trestini, Ilaria; Malleo, Giuseppe; Nappo, Gennaro; Ricci, Claudio; Ingaldi, Carlo; Vacca, Pier Giuseppe; De Pastena, Matteo; Secchettin, Erica; Zamboni, Giulia; Maggino, Laura; et al. (Frontiers in Nutrition, 2023)
Background & Aims: Body composition parameters and immunonutritional indexes provide useful information on the nutritional and inflammatory status of patients. We sought to investigate whether they predict the postoperative outcome in patients with pancreatic cancer (PC) who received neoadjuvant therapy (NAT) and then pancreaticoduodenectomy. Methods: Data from locally advanced PC patients who underwent NAT followed by pancreaticoduodenectomy between January 2012 and December 2019 in four high-volume institutions were collected retrospectively. Only patients with two available CT scans (before and after NAT) and immunonutritional indexes (before surgery) available were included. Body composition was assessed and immunonutritional indexes collected were: VAT, SAT, SMI, SMA, PLR, NLR, LMR, and PNI. The postoperative outcomes evaluated were overall morbidity (any complication occurring), major complications (Clavien-Dindo ≥ 3), and length of stay. Results: 121 patients met the inclusion criteria and constituted the study population. The median age at the diagnosis was 64 years (IQR16), and the median BMI was 24 kg/m2 (IQR 4.1). The median time between the two CT-scan examined was 188 days (IQR 48). Skeletal muscle index (SMI) decreased after NAT, with a median delta of -7.8 cm2/m2 (p < 0.05). Major complications occurred more frequently in patients with a lower pre-NAT SMI (p = 0.035) and in those who gained in subcutaneous adipose tissue (SAT) compartment during NAT (p = 0.043). Patients with a gain in SMI experienced fewer major postoperative complications (p = 0.002). The presence of Low muscle mass after NAT was associated with a longer hospital stay (Beta 5.1, 95%CI [1.5, 8.7], p = 0.006)). An increase in SMI from 35 to 40 cm2/m2 was a protective factor with respect to overall postoperative complications (OR 0.43, 95% [CI 0.21, 0.86], p < 0.001). None of the immunonutritional indexes investigated predicted the postoperative outcome. Conclusion: Body composition changes during NAT are associated with surgical outcome in PC patients who receive pancreaticoduodenectomy after NAT. An increase in SMI during NAT should be favored to ameliorate the postoperative outcome. Immunonutritional indexes did not show to be capable of predicting the surgical outcome.